The Effectiveness Of Using Dynamic Visualization In Natural Science Learning To Improve Students' Understanding In Junior High Schools - I Gde Wawan Sudatha; Alexander Hamonangan Simamora (Journal of Educational Science and Technology (EST), 2021)
Visualization can support an instructional process. Visualization consists of all types of nonverbal illustrations. The very rapidly computer technology enables the development of multimedia learning environment. This research was aimed at describing the effectiveness and attractiveness of the use of dynamic visualization in an instruction on transportation system and excretion in organisms. Sixty four students of grade 8 who consisted of 36 males and 28 females were used as the subjects of the research. The data of the research were collected in the form of pre-test and post-test scores in the students’ understanding of transportation system and excretion in organisms and in the attractiveness of the use of dynamic visualization in the instruction. Statistical test showed that the mean of the comprehension test before the use of dynamic visualization differed significantly from that after the use of dynamic visualization and that dynamic visualization was attractive to be used in the instruction. Hence, it can be concluded that dynamic visualization can enhance students’ understanding.